HYDROLYTIC ENZYME SYSTEMS OF Trichoderma spp.: FERMENTATION STRATEGIES, STRAIN ENGINEERING, AND SUSTAINABLE LIGNOCELLULOSIC VALORIZATION - Sri Helianty; Yuana Nurulita; Panca Setia Utama; Titania Tjandrawati Nugroho (BRIN - Badan Riset dan Inovasi Nasional, 2026)
Hydrolytic enzymes produced by Trichoderma spp. play a central role in lignocellulosic biomass conversion due to their high secretion capacity and catalytic versatility. This review provides a critical and integrated analyzes of enzyme systems, fermentation strategies, and bioprocess engineering approaches governing enzyme production and biomass valorization. A structured literature review was conducted using peer-reviewed publication 2019 to 2025. The analysis highlights synergistic interactions among cellulases, hemicellulases, and oxidative enzymes in overcoming biomass recalcitrance. Key process parameters—including aeration, moisture content, temperature regulation, and bioreactor design—are identified as a primary deteminants of productivity and efficiency. Solid-state fermentation is recognized as an efficient strategy for valorizing agricultural residues such as rice straw, although challenges in heat and mass transfer and scale-up remain. Advances in strain engineering, regulatory pathway optimization, and enzyme cocktail design improve hydrolytic performance, but trade-offs between productivity, stability, and process robustness persist. Integration within circular biorefinery frameworks is essential for scalable and sustainable biomass conversion.